U-Pb zircon xenocrysts dating as a proxy to assess volcanic assimilation and the underlying crust, Cretaceous Jaguarão Formation, RS, Brazil - Araújo,Vicente (2022)
Abstract The Early Cretaceous volcanic Jaguarão Formation formed duringthe early stages of Gondwana breakup. These felsic rocks characteristically enclose numerous crustal xenoliths. Fieldwork, petrographic studies, and laser ablation multicollector ion coupled plasma mass spectrometer (LA-ICP-MS) U-Pb analyses were carried out to evaluate the xenoliths of the Jaguarão Formation. A base-to-top distribution of xenoliths in the different flows of the volcanic pile indicates that earlier flows incorporated centimeter-sized fragments of local underlying gneiss, granite, and quartz veins, with limited assimilation. In the middle part of the volcanic pile, the size of the xenoliths is smaller and assimilation textures are more frequent. At this same level, reequilibrated orthopyroxene and plagioclase antecrysts were recognized, suggesting fractionation coeval with assimilation in a lower magmatic chamber prior to extrusion. At the top, no visible xenoliths occur. U-Pb ages of the zircon xenocrysts served as a proxy for assessing the crust underlying the volcanic rocks. Most of the ages obtained are similar to the ages of the Eastern Dom Feliciano Belt cropping out nearby, ranging from 680 to 620 Ma, with a subordinate group ranging from 580 to 570 Ma, suggesting a shallow crust contribution. The presence of few Paleoproterozoic and Mesoproterozoic (1.0-1.2 Ma) zircons, however, suggeststhat the underlying terrain may be more complex..